(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
In this article, an electricity efficiency of the synthorids of Maleine Angiirid was identified 1M HCL + 200 mg / l naCl and 0.5 HCL + 200 mg / l naCl. The Inhibition Efficiency Was 93.15% and 92.86%, Respective.